Factors that Correlate Between Dividend Signaling and Dividend Acceleration Through Digital Investment Among Online Investors in Iligan City - Aguilar, Jay Cob; Perion, Jenvy; Sanchez, Lady Lou; Abiol, Michael Jere (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Digital investments are becoming mainstream but must be secured to avoid sudden loss. This study measures the correlation between dividend signaling and acceleration through digital assets among online jobbers in Iligan City. It has become a full-fledged investment tool, creating a new, booming market with unknown potential. Thanks to the Internet, many businesses are interconnected worldwide, which sparked the industrial revolution centered on globalization. Several solutions have been developed to provide fast and low-cost payments globally in the Philippines, but third parties manage these payments. Cryptocurrency has drawn the attention of online jobbers during the lockdown, but many people need to learn what they can do for financial services or start investing. This research employed a descriptive correlational research design to describe the profile of respondents in terms of age, gender, salary, Investment capital, and length of the Investment. It was a correlation to determine the relationship between demographic profiles and dividend signaling in dividend acceleration. Only those online Investors who were available and signified their interest in participating in the study were included as the sources of the respondents. The research environment of this study covered online Investors in Iligan City. This study examines how investing in digital Investment has become a full-fledged investment tool, enabling rapid and low-cost payments worldwide. It is recognized in the market for dividend signaling and acceleration, but many people hesitate to start investing. Some of the biggest financial companies still need to build and launch digital investment solutions, creating a new, booming market with unknown potential.